Polydimethylsiloxane-coated macroporous silica adsorbent in thermal desorption gas chromatography - Ikuo Ueta; Mizuki Hayashibe; Katsunori Sumiya; Yuki Ariizumi; Koji Fujimura; Yoshihiro Saito (Journal of Chromatography Open, 2023)
Polydimethylsiloxane (PDMS)-coated macroporous silica (MPSi) particles were developed for the extraction of volatile organic compounds (VOCs) from air samples in thermal desorption-gas chromatographic analysis. The gas sample was collected by a gas sampling pump at 100 mL/min. Different amounts of PDMS coating were prepared, and the fundamental extraction and desorption performances were investigated using even numbered n-alkanes of C8–C28. The extraction efficiency increased by increasing PDMS coating, and the desorption efficiency showed more than 99% at a desorption temperature of 310°C for all the investigated adsorbents. This remarkable desorption performance showed a higher peak area of the analytes than that of the Tenax TA-packed thermal desorption tube, especially for higher molecular weight compounds. Furthermore, an activated carbon particle of Carbopack X was introduced on the latter side of the PDMS-MPSi to extract low-molecular weight compounds. This double-bed-type extraction tube showed a successful determination of a wide range of VOCs. The double-bed-type extraction tube was then applied to the extraction of VOCs related to sick building syndrome (SBS). The results for the extraction and desorption performances of the SBS-related VOCs were well agreed with that of alkanes, and the applicability of the extraction tube to the determination of other types of conventional VOCs were confirmed.